2008
DOI: 10.1093/ije/dyn121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cause-of-death statistics for Brazil, 2002–2004

Abstract: There is considerable heterogeneity in the quality of cause-of-death statistics across Brazilian regions, especially for criteria such as completeness and ill-defined causes. These factors can influence generalizability and validity of reported causes of death, and must be considered in the interpretation and use of data for secondary descriptive analyses such as burden of disease estimation at regional level, with suitable adjustments to account for bias. The differences identified in this study could be a us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
73

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(180 citation statements)
references
References 15 publications
1
106
0
73
Order By: Relevance
“…However, there are still regional differentials regarding the completeness of death registration and the inadequate recording of causes of death 9 .…”
Section: Palavras-chavementioning
confidence: 99%
“…However, there are still regional differentials regarding the completeness of death registration and the inadequate recording of causes of death 9 .…”
Section: Palavras-chavementioning
confidence: 99%
“…In 2003, road traffic crashes in Brazil were responsible for over 26 percent of fatal injuries (rate of 17 per 100,000 population; Gawryszewski and Rodrigues 2006). The most commonly affected population in road traffic fatalities was found to be males in the "20 to 29 year old" age group (Franca et al 2008). Reichenheim et al (2011) showed using Brazil's Ministry of Health's mortality database that pedestrians account for nearly 35 percent of traffic deaths, with a mortality rate of just over 6 per 100,000 in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…A cobertura e a qualidade das informações sobre causas de óbito são desiguais entre as regiões brasileiras e, apesar de importante decréscimo observado na proporção de óbitos por causa mal definida nos últimos anos, as regiões Norte e Nordeste ainda apresentam níveis muito elevados 5 .…”
Section: Introductionunclassified